Exocyst complexes multiple functions in plant cells secretory pathways - Zárský, Viktor; Kulich, Ivan; Fendrych, Matyáš; Pečenková, Tamara (Current opinion in plant biology, 2013)
The exocyst is a complex of proteins mediating first contact (tethering) between secretory vesicles and the target membrane. Discovered in yeast as an effector of RAB and RHO small GTPases, it was also found to function in land plants. Plant cells and tissues rely on targeted exocytosis and this implies that the exocyst is involved in regulation of cell polarity and morphogenesis, including cytokinesis, plasma membrane protein recycling (including PINs, the auxin efflux carriers), cell wall biogenesis, fertilization, stress and biotic interactions including defence against pathogens. The dramatic expansion of the EXO70 subunit gene family, of which individual members are likely responsible for exocyst complex targeting, implies that there are specialized functions of different exocysts with different EXO70s. One of these functions comprises a role in autophagy-related Golgi independent membrane trafficking into the vacuole or apoplast. It is also possible, that some EXO70 paralogues have been recruited into exocyst independent functions. The exocyst has the potential to function as an important regulatory hub to coordinate endomembrane dynamics in plants.
Keywords: Exocytosis; vezikulární transportní proteiny; signální transdukce; Vesicular Transport Proteins; Protein Binding; Golgiho aparát; Signal Transduction; Plant Cells; Secretory Pathway; rostlinné proteiny; Models, Biological; exocytóza; sekreční dráha; Plant Proteins; vazba proteinů; biologické modely; rostlinné buňky; Arabidopsis; Golgi Apparatus